Polyamide Composition

The polyamide composition, featuring a specific blend of polyamides, branched polyamines, sterically hindered phenols, and dyes, addresses the challenge of achieving long-term heat-resistant aging and high electrical properties while maintaining appearance and preventing additive bleed-out, demonstrating enhanced performance in high-temperature and humid conditions.

JP7670840B2Active Publication Date: 2025-04-30ASAHI KASEI KOGYO KABUSHIKI KAISHA

Patent Information

Application Number
JP2023545638
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-07
Filing Date
2022-08-31
Publication Date
2025-04-30
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

Existing polyamide compositions struggle to simultaneously achieve long-term heat-resistant aging at 180°C, high electrical properties, and maintain appearance without additive bleed-out, especially in high-temperature and humid environments.

Method used

A polyamide composition comprising 100 parts by mass of polyamide, 0.1 to 3 parts by mass of branched polyamines, 0.05 to 3 parts by mass of sterically hindered phenols, and 0.01 to 0.5 parts by mass of azine or phthalocyanine dyes, with a halide ion concentration of 500 ppm or less, optimized with polyethyleneimine and carbon black for improved heat and electrical properties.

Benefits of technology

The composition exhibits excellent mechanical, heat-resistant aging, and electrical properties for up to 2000 hours at 180°C, suppresses additive bleed-out at 80°C and 95% relative humidity, and maintains a superior appearance, making it suitable for high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670840000001
    Figure 0007670840000001
  • Figure 0007670840000002
    Figure 0007670840000002
  • Figure 0007670840000003
    Figure 0007670840000003
Patent Text Reader

Abstract

The present invention provides a polyamide composition and the like, said polyamide composition including (A) a polyamide, and, relative to 100 parts by mass of (A) the polyamide, 0.1 to 3 parts by mass of (B) a branched polyamine, 0.05 to 3 parts by mass of (C) a sterically hindered phenol, and 0.01 to 0.5 parts by mass of (D) an azine dye or a phthalocyanine dye, wherein the concentration of (F) halide ions measured via combustion ion chromatography is 500 ppm by mass or less relative to the total mass of the polyamide composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide composition. [Background technology]

[0002] Polyamide has excellent strength, heat resistance, chemical resistance, and specific gravity, which means that it has a lower specific gravity than metals, and therefore has been used as a substitute for metals in automobile mechanical parts and the like.

[0003] Some automotive parts are exposed to high-temperature environments for long periods of time. In such cases, the part materials are required to have thermal stability (hereinafter referred to as "long-term heat aging resistance") that allows them to maintain their strength even when placed in high-temperature environments for long periods of time. Furthermore, with the electrification of automobiles and the shift to EVs, there are also parts that have electronic contacts and are exposed to high-temperature environments (for example, 180°C or lower). Materials used in such parts are required to have long-term heat aging resistance at 180°C and high electrical properties (for example, volume resistivity and tracking resistance).

[0004] Copper halides and alkali metal halides used in combination with copper halides are known as heat stabilizers used in polyamides (see, for example, Patent Document 1, etc.). However, while the addition of these heat stabilizers is highly effective as heat stabilizers, there is a problem that the halide ions contained in the heat stabilizers cause a decrease in electrical resistivity and tracking resistance. Due to the above constraints, it is difficult to achieve both long-term heat aging resistance at 180°C and high electrical resistivity and high tracking resistance, and this is still being actively studied.

[0005] In light of the above, there is a need for a polyamide material that simultaneously satisfies all of the requirements for long-term heat aging resistance at 180°C, high electrical properties, and good appearance.

[0006] As a technique for improving the long-term heat aging resistance of polyamide without impairing its electrical properties, a method of using an organic heat stabilizer such as sterically hindered phenol, aromatic amine, or sterically hindered amine is known. However, when an organic heat stabilizer is used alone, the heat aging resistance at 180°C is insufficient. In addition, if the amount of organic heat stabilizer added is increased to improve the long-term heat aging resistance, there is a problem that the additive bleeds out from the molded product, impairing the appearance.

[0007] On the other hand, as a technique for improving the long-term heat aging resistance of polyamide resins, a method of adding polyethyleneimine to polyamide as an effective heat stabilizer is known (see, for example, Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 8-325382 [Patent Document 2] JP 2019-116607 A [Patent Document 3] Special Publication No. 2012-512301 Summary of the Invention [Problem to be solved by the invention]

[0009] However, Patent Documents 2 and 3 only show examples of using copper halides in combination. Halide ions cause a decrease in electrical properties. Furthermore, Patent Documents 2 and 3 do not specifically discuss examples of using additives that absorb laser light. That is, a polyamide resin composition that is excellent in long-term heat aging resistance and electrical properties, has excellent appearance, and suppresses bleed-out of additives has not yet been obtained.

[0010] The present invention has been made in view of the above circumstances, and provides a polyamide composition which is excellent in mechanical properties, heat aging resistance at 180°C for a long period of about 2000 hours, and electrical properties, in which bleed-out of additives is suppressed at 80°C and a relative humidity of 95%, additives are unlikely to dissolve in water, and which can give molded articles with excellent appearance. [Means for solving the problem]

[0011] That is, the present invention includes the following aspects. (1)(A) a polyamide; Relative to 100 parts by mass of the (A) polyamide, 0.1 parts by mass or more and 3 parts by mass or less of a branched polyamine (B); 0.05 parts by mass or more and 3 parts by mass or less of (C) a sterically hindered phenol; (D) azine dye or phthalocyanine dye in an amount of 0.01 part by mass or more and 0.5 part by mass or less; A polyamide composition comprising: A polyamide composition, having a concentration of (F) halide ions of 500 mass ppm or less relative to the total mass of the polyamide composition as measured by combustion ion chromatography. (2) The polyamide composition according to (1), wherein the (A) polyamide contains polyamide 66 and the content of polyamide 66 is 50 mass% or more based on the total mass of the (A) polyamide. (3) The polyamide composition according to (1) or (2), wherein the branched polyamine (B) is a polyethyleneimine homopolymer or copolymer (Ba). (4) The polyamide composition according to any one of (1) to (3), wherein the branched polyamine (B) has a weight average molecular weight of 400 or more and 2,000 or less. (5) The polyamide composition according to any one of (1) to (4), wherein the (C) sterically hindered phenol contains one or more amide groups. (6) The polyamide composition according to any one of (1) to (5), further comprising (E) 0.01 part by mass or more and 0.5 part by mass or less of carbon black relative to 100 parts by mass of the polyamide (A). (7) The polyamide composition according to any one of (1) to (6), wherein a concentration of (F) halide ions, relative to the mass of (D) the azine dye or the phthalocyanine dye, as measured by combustion ion chromatography, is less than 1 mass%. (8) The polyamide composition according to any one of (1) to (7), wherein a weight ratio of the (B) branched polyamine to the (C) sterically hindered phenol is 0.06 to 30, and a weight ratio of the (C) sterically hindered phenol to the (D) azine dye or phthalocyanine dye is 0.5 to 60. (9) The polyamide composition according to any one of (1) to (8), further comprising (G) a filler. (10) (A) a polyamide; A polyamide composition comprising: 100 parts by mass of the polyamide (A); and 0.1 parts by mass or more and 3 parts by mass or less of a branched polyamine (B), The polyamide composition, wherein the viscosity of the branched polyamine (B) at 20°C, as measured by a Brookfield viscometer in accordance with ISO 2555, is 1000 mPa·s or more and 2500 mPa·s or less. (11) The polyamide composition according to (10), wherein the (A) polyamide contains polyamide 66, and the content of the polyamide 66 is 50 mass% or more based on the total mass of the (A) polyamide. (12) The polyamide composition according to (10) or (11), wherein the branched polyamine (B) is a polyethyleneimine homopolymer or copolymer (Ba). (13) The polyamide composition according to any one of (10) to (12), wherein the branched polyamine (B) has a weight average molecular weight of 400 or more and 2,000 or less. (14) The polyamide composition according to any one of (10) to (13), further comprising 0.05 parts by mass or more and 3 parts by mass or less of an organic heat stabilizer (C) relative to 100 parts by mass of the polyamide (A). (15) The polyamide composition according to (14), wherein the (C) organic heat stabilizer is (C1) a sterically hindered phenol. (16) The polyamide composition according to (15), wherein the (C1) sterically hindered phenol contains one or more amide groups. (17) The polyamide composition according to any one of (10) to (16), further comprising (D) an azine dye or a phthalocyanine dye. (18) The polyamide composition according to (17), wherein the concentration of (F) halide ions, relative to the mass of (D) the azine dye or phthalocyanine dye, as measured by combustion ion chromatography, is less than 1 mass%. (19) The polyamide composition according to any one of (10) to (18), further comprising (E) carbon black in an amount of 0.001 part by mass or more and 0.5 part by mass or less relative to 100 parts by mass of the (A) polyamide. (20) The polyamide composition according to any one of (10) to (19), wherein a concentration of (F) halide ions relative to the total mass of the polyamide composition as measured by combustion ion chromatography is 500 ppm by mass or less. (21) The polyamide composition according to any one of claims 10 to 20, further comprising (G) a filler. Effect of the Invention

[0012] The polyamide composition of the above aspect has excellent mechanical properties, heat aging resistance at 180°C for a long period of about 2000 hours, and electrical properties, and additive bleed-out at 80°C and a relative humidity of 95% is suppressed, so that the additive is less likely to dissolve in water, and a molded product with excellent appearance can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out by appropriately modifying it within the scope of its gist.

[0014] In this specification, the term "polyamide" refers to a polymer having an amide (-NHCO-) ​​group in the main chain.

[0015] <Polyamide composition (1)> The polyamide composition of one embodiment of the present invention comprises: (A) a polyamide; Relative to 100 parts by mass of the (A) polyamide, 0.1 parts by mass or more and 3 parts by mass or less of a branched polyamine (B); 0.05 parts by mass or more and 3 parts by mass or less of (C) a sterically hindered phenol; (D) an azine dye or a phthalocyanine dye in an amount of 0.01 parts by mass or more and 0.5 parts by mass or less; Includes.

[0016] In addition, the concentration of (F) halide ions relative to the total mass of the polyamide composition as measured by combustion ion chromatography is 500 ppm by mass or less.

[0017] The polyamide composition of the present embodiment has the above-mentioned configuration, and thus has excellent heat aging resistance at 180°C for a long period of about 2000 hours, excellent electrical properties, and inhibits bleed-out of additives at 80°C and a relative humidity of 95%, and can give molded articles with excellent appearance and laser marking properties.

[0018] In the following description, the above (A) polyamide, (D) azine dye or phthalocyanine dye, and (F) halide ion may be referred to as components (A) to (D) and component (F), respectively.

[0019] Each component of the polyamide composition of the present embodiment will be described in detail below.

[0020] <(A) Polyamide> Examples of the polyamide (A) include (a-1) polyamide obtained by ring-opening polymerization of lactam, (a-2) polyamide obtained by self-condensation of ω-aminocarboxylic acid, (a-3) polyamide obtained by condensing diamine and dicarboxylic acid, and copolymers thereof, etc. The polyamide may be used alone or in combination of two or more kinds.

[0021] (a-1) Lactams used in the production of polyamides include, but are not limited to, pyrrolidone, caprolactam, undecalactam, dodecalactam, and the like. (a-2) The ω-aminocarboxylic acid used in the production of the polyamide is not limited to the following, but examples thereof include ω-amino fatty acids which are ring-opening compounds of the above-mentioned lactams with water. Furthermore, two or more kinds of the lactam or ω-aminocarboxylic acid may be used in combination and condensed.

[0022] (a-3) Diamines (monomers) used in the production of polyamides include, but are not limited to, linear aliphatic diamines, branched aliphatic diamines, alicyclic diamines, and aromatic diamines. Examples of linear aliphatic diamines include, but are not limited to, hexamethylenediamine and pentamethylenediamine. Examples of branched aliphatic diamines include, but are not limited to, 2-methylpentanediamine and 2-ethylhexamethylenediamine. Examples of alicyclic diamines include, but are not limited to, cyclohexanediamine, cyclopentanediamine, and cyclooctanediamine. Examples of aromatic diamines include, but are not limited to, p-phenylenediamine and m-phenylenediamine. (a-3) Dicarboxylic acids (monomers) used in the production of polyamides include, but are not limited to, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, aromatic dicarboxylic acids, and the like. Examples of the aliphatic dicarboxylic acid include, but are not limited to, adipic acid, pimelic acid, and sebacic acid. The alicyclic dicarboxylic acid is not limited to the following, but may be, for example, cyclohexanedicarboxylic acid. Examples of aromatic dicarboxylic acids include, but are not limited to, phthalic acid and isophthalic acid. The diamines and dicarboxylic acids as the monomers mentioned above may be condensed either alone or in combination of two or more kinds.

[0023] Specific examples of polyamides contained in the polyamide composition include polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecane amide), polyamide 12 (polydodecane amide), polyamide 46 (polytetramethylene adipamide), polyamide 56 (polypentamethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyhexamethylene dodecamide), polyamide 6T (polyhexamethylene terephthalamide), polyamide 9T (polynonamethylene terephthalamide), and copolymer polyamides containing these as constituent components. Among them, polyamides are preferably polyamide 66 (PA66), polyamide 6 (PA6), polyamide 610 (PA610), or polyamide 612 (PA612). PA66 is a suitable material for automobile parts because of its excellent heat resistance, moldability, and toughness. In addition, long-chain aliphatic polyamides such as PA610 and PA612 have excellent chemical resistance.

[0024] Furthermore, from the viewpoints of heat resistance, moldability, and toughness, the content of PA66 relative to the total mass of the polyamide (A) is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 70 mass% or more, even more preferably 80 mass% or more, particularly preferably 90 mass% or more, and most preferably 100 mass% or more.

[0025] [End-capping agent] The ends of the (A) polyamide may be capped with a known end-capping agent. Such an end-capping agent can also be added as a molecular weight regulator when producing a polyamide from the above dicarboxylic acid, the above diamine, and, if necessary, at least one of the above lactam and the above aminocarboxylic acid.

[0026] Examples of the terminal blocking agent include, but are not limited to, monocarboxylic acid, monoamine, acid anhydride, monoisocyanate, monoacid halide, monoester, monoalcohol, etc. Examples of the acid anhydride include, but are not limited to, phthalic anhydride, etc. These terminal blocking agents may be used alone or in combination of two or more. Among these, the terminal blocking agent is preferably a monocarboxylic acid or a monoamine. By blocking the terminals of the polyamide with the terminal blocking agent, the polyamide composition tends to have better thermal stability.

[0027] The monocarboxylic acid usable as the end-capping agent may be any one that is reactive with amino groups that may be present at the terminals of the polyamide. Specific examples of the monocarboxylic acid include, but are not limited to, aliphatic monocarboxylic acids, alicyclic monocarboxylic acids, and aromatic monocarboxylic acids. Examples of aliphatic monocarboxylic acids include, but are not limited to, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid. Examples of alicyclic monocarboxylic acids include, but are not limited to, cyclohexane carboxylic acid. Examples of aromatic monocarboxylic acids include, but are not limited to, benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid. These monocarboxylic acids may be used alone or in combination of two or more kinds.

[0028] The monoamine usable as the end-capping agent may be any monoamine that is reactive with a carboxyl group that may be present at the end of the polyamide. Specific examples of the monoamine include, but are not limited to, aliphatic monoamines, alicyclic monoamines, and aromatic monoamines. Examples of the aliphatic amine include, but are not limited to, methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine. Examples of alicyclic amines include, but are not limited to, cyclohexylamine, dicyclohexylamine, and the like. Examples of aromatic amines include, but are not limited to, aniline, toluidine, diphenylamine, naphthylamine, and the like. These monoamines may be used alone or in combination of two or more kinds.

[0029] A polyamide composition containing (A) a polyamide end-capped with an end-capping agent tends to have better heat resistance, flowability, toughness, low water absorbency and rigidity.

[0030] [(A) Polyamide content] The amount of polyamide (A) in the polyamide composition can be, for example, 40.0 mass% or more and 99.8 mass% or less, for example, 50.0 mass% or more and 90.0 mass% or less, for example, 55.0 mass% or more and 80.0 mass% or less, based on the total mass of the polyamide.

[0031] [(A) Method for producing polyamide] In producing the (A) polyamide, the amount of dicarboxylic acid and the amount of diamine added are preferably approximately the same molar amount. Taking into consideration the amount of diamine that escapes to the outside of the reaction system during the polymerization reaction, the molar amount of the total diamine relative to the total molar amount of dicarboxylic acid is preferably 0.9 to 1.2, more preferably 0.95 to 1.1, and even more preferably 0.98 to 1.05.

[0032] (A) A method for producing a polyamide includes, but is not limited to, for example, a step of polymerizing a dicarboxylic acid constituting a dicarboxylic acid unit, a diamine constituting a diamine unit, and, as necessary, at least one of a lactam constituting a lactam unit and an aminocarboxylic acid constituting an aminocarboxylic acid unit to obtain a polymer. In addition, the method for producing a polyamide preferably further comprises a step of increasing the degree of polymerization of the polyamide. If necessary, the method may include a step of capping the ends of the resulting polymer with an end-capping agent.

[0033] Specific methods for producing polyamide include various methods as exemplified by the following 1) to 4). 1) A method in which an aqueous solution of a dicarboxylic acid-diamine salt or a mixture of a dicarboxylic acid and a diamine, or an aqueous suspension of these, is heated and polymerized while maintaining the molten state (hereinafter sometimes referred to as the "thermal melt polymerization method"). 2) A method in which the degree of polymerization of polyamide obtained by hot melt polymerization is increased while maintaining the polyamide in a solid state at a temperature below the melting point (hereinafter sometimes referred to as "hot melt polymerization / solid-state polymerization method"). 3) A method of polymerizing a dicarboxylic acid-diamine salt or a mixture of a dicarboxylic acid and a diamine while maintaining it in a solid state (hereinafter, sometimes referred to as a "solid-phase polymerization method"). 4) A method of polymerization using a dicarboxylic acid halide component equivalent to a dicarboxylic acid and a diamine component (hereinafter sometimes referred to as the "solution method"). Among them, a specific method for producing polyamide is preferably a production method including a hot melt polymerization method. When producing polyamide by hot melt polymerization, it is preferable to maintain the molten state until the polymerization is completed. As a method for maintaining the molten state, for example, a method of producing polyamide under polymerization conditions suitable for its composition can be mentioned. As the polymerization conditions, for example, the following conditions can be mentioned. First, the polymerization pressure in the hot melt polymerization method is set to 14 kg / cm 2 More than 25kg / cm 2 Heating is continued while controlling the pressure in the vessel to below atmospheric pressure (gauge pressure is 0 kg / cm 2 ), a polyamide having the desired composition can be obtained.

[0034] In the method for producing a polyamide, the polymerization form is not particularly limited, and may be a batch type or a continuous type. The polymerization apparatus used for producing the polyamide is not particularly limited, and any known apparatus can be used, such as an autoclave type reactor, a tumbler type reactor, or an extruder type reactor such as a kneader.

[0035] Hereinafter, as a method for producing polyamide, a method for producing polyamide by a batch-type hot melt polymerization method will be specifically described, but the method for producing polyamide is not limited thereto. First, an aqueous solution containing about 40% by mass or more and about 60% by mass or less of raw material components of polyamide (dicarboxylic acid, diamine, and, as necessary, at least one of lactam and aminocarboxylic acid) is concentrated to about 65% by mass or more and about 90% by mass or less in a concentration tank operated at a temperature of 110°C to 180°C and a pressure of about 0.035 MPa to 0.6 MPa (gauge pressure) to obtain a concentrated solution. Next, the concentrated solution obtained is transferred to an autoclave, and heating is continued until the pressure in the autoclave becomes about 1.2 MPa or more and 2.2 MPa or less (gauge pressure). Thereafter, in the autoclave, the pressure is maintained at about 1.2 MPa to 2.2 MPa (gauge pressure) while removing at least one of the water and gas components, and when the temperature reaches about 220°C to 260°C, the pressure is reduced to atmospheric pressure (gauge pressure: 0 MPa). After the pressure inside the autoclave is reduced to atmospheric pressure, the pressure can be reduced as necessary to effectively remove the by-produced water. The autoclave is then pressurized with an inert gas such as nitrogen, and the polyamide melt is extruded from the autoclave as a strand. The extruded strand is cooled and cut to obtain polyamide pellets.

[0036] [(A) Polyamide polymer end] The polymer ends of the (A) polyamide are not particularly limited, but can be classified and defined as follows: That is, 1) the amino terminus, 2) the carboxy terminus, 3) the terminus provided by a capping agent, and 4) other terminus. 1) The amino terminal is a polymer end having an amino group (-NH2 group) and originates from the diamine unit of the raw material. 2) The carboxyl end is a polymer end having a carboxyl group (-COOH group) and originates from the dicarboxylic acid used as the raw material. 3) The term "terminals formed by a capping agent" refers to terminals formed when a capping agent is added during polymerization. Examples of the capping agent include the above-mentioned terminal capping agents. 4) The other terminals are polymer terminals not classified into the above 1) to 3). Specific examples of the other terminals include terminals generated by deammonia reaction of amino terminals, terminals generated by decarboxylation of carboxy terminals, etc.

[0037] [(A) Characteristics of polyamide] ((A) Molecular weight of polyamide) The weight average molecular weight Mw can be used as an index of the molecular weight of polyamide. The weight average molecular weight Mw of polyamide can be, for example, 10,000 or more and 100,000 or less, for example, 15,000 or more and 95,000 or less, for example, 20,000 or more and 90,000 or less, for example, 25,000 or more and 85,000 or less. The weight average molecular weight Mw can be measured by gel permeation chromatography (GPC) as described in the following Examples.

[0038] (A) Molecular weight distribution of polyamide The molecular weight distribution of polyamide is indicated by the weight average molecular weight Mw / number average molecular weight Mn. The Mw / Mn of the polyamide may be 1.8 or more, such as 1.8 or more and 3.0 or less, such as 1.9 or more and 2.5 or less.

[0039] Examples of methods for controlling the Mw / Mn of a polyamide within the above range include a method of adding a known polycondensation catalyst such as phosphoric acid or sodium hypophosphite as an additive during the thermal melt polymerization of the polyamide, and a method of controlling polymerization conditions such as heating conditions and reduced pressure conditions. The Mw / Mn of a polyamide can be calculated using the weight average molecular weight Mw and the number average molecular weight Mn obtained using GPC, as described in the Examples below.

[0040] <(B) Branched polyamine> (B) Examples of branched polyamines include polyalkyleneimines and polyalkylenepolyamines. Examples of polyalkyleneimines include polyethyleneimine and polytrimethyleneimine.

[0041] Among the branched polyamines (B), polyethyleneimine homopolymers or copolymers (Ba) are particularly preferred in terms of heat aging resistance and strength and appearance of molded products.

[0042] "Polyethyleneimines" in this specification are homopolymers and copolymers obtainable by the methods described in the electronic version of UllMann under the keyword "aziridine" or in WO 94 / 012560 (Reference 1). Hereinafter, "(Ba) polyethyleneimine homopolymer or copolymer" may be referred to as "(Ba) polyethyleneimine".

[0043] Generally, the homopolymers of ethyleneimine are obtained by polymerization of ethyleneimine (aziridine) in aqueous or organic solution in the presence of an initiator, an acid or a Lewis acid. The homopolymer of ethyleneimine obtained by such a method is generally a branched polymer containing primary, secondary and tertiary amino groups in a molar ratio of primary amino groups:secondary amino groups:tertiary amino groups=approximately 30%:40%:30%. The distribution of amino groups is 13 It can be measured using C-NMR spectroscopy.

[0044] Comonomers for forming copolymers of ethyleneimine include amines having at least two amino groups, as described above. The comonomer is not limited to the following, but may be, for example, an alkylenediamine having 2 to 10 carbon atoms in the alkylene group. In particular, ethylenediamine or propylenediamine is preferred. In addition to the above, examples of the comonomer include diethylenetriamine, triethylenetetramine, tetraethylenepentamine, dipropylenetriamine, tripropylenetetramine, dihexamethylenetriamine, aminopropylethylenediamine, and bisaminopropylethylenediamine.

[0045] In addition to the above, the (Ba) polyethyleneimine is preferably a crosslinkable polyethyleneimine obtained by reacting polyethyleneimine with a bifunctional or polyfunctional crosslinking agent having, as a functional group, at least one selected from the group consisting of a halogenhydrin, a glycidyl, an aziridine, an isocyanate unit, and a halogen atom. Examples of such compounds include epichlorohydrin; bischlorohydrin ethers composed of polyalkylene glycol and 2 to 100 units selected from the group consisting of ethylene oxide units and propylene oxide units, and compounds described in German Patent Application Publication No. 19931720 (Reference 2) and U.S. Pat. No. 4,144,123 (Reference 3). As a method for producing crosslinked polyethyleneimine, the methods described in the above references, European Patent Application Publication No. 0895521 (Reference 4) and European Patent Application Publication No. 0025515 (Reference 5) can be applied.

[0046] Furthermore, as the polyethyleneimine (Ba), grafted polyethyleneimine is also preferred. As the grafting agent, any compound capable of reacting with the amino or imino group of polyethyleneimine can be used. As a method for producing the grafting agent and the grafted polyethyleneimine, for example, the method described in European Patent Application Publication No. 0675914 (Reference 6) can be applied.

[0047] Also, (Ba) polyethyleneimine may be amidated by reaction with a carboxylic acid, a carboxylic acid ester or anhydride, a carboxylic acid amide, or a carboxylic acid halide. Depending on the proportion of amidated nitrogen atoms in the polyethyleneimine chain, the amidated polymer may be subsequently crosslinked with a predetermined crosslinking agent. In this case, up to 30 mol% of the amino functional groups are amidated so that at least one atom selected from the group consisting of primary nitrogen atoms and secondary nitrogen atoms can still be sufficiently supplied for the subsequent crosslinking reaction. That is, in order to ensure that at least one atom selected from the group consisting of primary nitrogen atoms and secondary nitrogen atoms is present in a sufficient amount in the amidated polymer, it is preferable that the amino functional groups in the amidated polymer are amidated at a proportion of 30 mol% or less. In addition, all of the carboxylic acids are consumed by the amidation, and the amidated polymer has no carboxylic acid terminal group, so that it can be clearly distinguished from organic acids.

[0048] The (Ba) polyethyleneimine may also be an alkoxylated polyethyleneimine obtained by reacting polyethyleneimine with at least one selected from the group consisting of ethylene oxide and propylene oxide. Such an alkoxylated polymer can then be crosslinked.

[0049] Also, from the viewpoint of affinity with polyamide resin, (Ba) polyethyleneimine may be, for example, a hydroxyl group-containing polyethyleneimine and an amphoteric polyethyleneimine (anionic group incorporated), and generally, a lipophilic polyethyleneimine obtained by incorporating a long-chain hydrocarbon group into the polymer chain. Methods for producing such polyethyleneimine polymers are known to those skilled in the art.

[0050] [Characteristics of (Ba) polyethyleneimine] ((Ba) Weight average molecular weight of polyethyleneimine) The weight average molecular weight of the polyethyleneimine (Ba) is preferably 100 or more and 3,000,000 or less, more preferably 200 or more and 2,000,000 or less, even more preferably 300 or more and 20,000 or less, particularly preferably 400 or more and 2,000 or less, and most preferably 700 or more and 1,000 or less. When the weight-average molecular weight of the polyethyleneimine (Ba) is equal to or greater than the above lower limit, the heat aging resistance can be improved, whereas when the weight-average molecular weight of the polyethyleneimine (Ba) is equal to or less than the above upper limit, the appearance of a molded article can be improved. The weight average molecular weight of the polyethyleneimine (Ba) can be measured by a light scattering method.

[0051] ((Ba) Viscosity of Polyethyleneimine) The viscosity of the polyethyleneimine (Ba) is preferably 1000 mPa·s or more and 2500 mPa·s or less, more preferably 1200 mPa·s or more and 2300 mPa·s or less, even more preferably 1200 mPa·s or more and 2100 mPa·s or less, and particularly preferably 1400 mPa·s or more and 1900 mPa·s or less. When the viscosity of the polyethyleneimine (Ba) is at least the above lower limit, the heat aging resistance and mechanical properties become better. When the viscosity of the polyethyleneimine (Ba) is not more than the above upper limit, the heat aging resistance and appearance of a molded article formed from the polyethyleneimine (Ba) will be better, and the polyethyleneimine (B) contained in the molded article will be less likely to dissolve in water. The viscosity of the polyethyleneimine (Ba) can be measured at 20° C. using a Brookfield viscometer in accordance with ISO 2555.

[0052] [(Ba) Polyethyleneimine content] In the polyamide composition of this embodiment, from the viewpoints of heat aging resistance, appearance, strength and rigidity when formed into a molded article, the content of (Ba) polyethyleneimine is from 0.1 to 3 parts by mass, preferably from 0.2 to 2 parts by mass, and more preferably from 0.3 to 1.4 parts by mass, per 100 parts by mass of (A) polyamide. When the content of (Ba) polyethyleneimine is equal to or more than the above lower limit, the heat aging resistance and the appearance are improved, whereas when the content of (Ba) polyethyleneimine is equal to or less than the above upper limit, the strength, rigidity, etc. of the molded article are improved.

[0053] <(C) Sterically hindered phenol> The polyamide composition of the present embodiment contains (C) a sterically hindered phenol, and therefore has excellent heat aging resistance when molded into a molded article, and can suppress bleed-out of additives at 80°C and a relative humidity of 95%.

[0054] (C) Examples of sterically hindered phenols include, but are not limited to, N,N'-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide], triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,4-bis-(n -Octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2-thiobis(4-methyl-6-1-butylphenol), N,N'-hexamethion Benzenebis(3,5-di-tert-butyl-4-hydroxy-hydroxy-namamid), 3,5-di-tert-butyl-4-hydroxy-benzylphosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-tert-butyl-4-hydroxybenzylsulfonate calcium ethyl, tris-(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 2,6-di-tert-butyl-p-cresol, Butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, stearyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-tert-butylphenol), 4,4'-thiobis-(3-methyl-6-tert-butylphenol), octylated diphenylamine, 2,4-bis[(octylthio)methyl]-o-cresol, isooctyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol, 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane , 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, bis[3,3'-bis-(4'-hydroxy-3'-tert-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-sec-triazine-2,4,6-(1H,3H,5H)trione, d-α-tocopherol, etc.

[0055] Among the (C) sterically hindered phenols listed above, sterically hindered phenols having one or more amide groups are preferred, and N,N'-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide] is more preferred. (C) sterically hindered phenols having one or more amide groups interact more strongly with (D) azine dyes or phthalocyanine dyes than (C) sterically hindered phenols having no amide groups, thereby more effectively suppressing the bleeding out of (C) sterically hindered phenols.

[0056] [(C) Content of sterically hindered phenols] In the polyamide composition of this embodiment, from the viewpoint of heat aging resistance and suppression of bleed-out when formed into a molded article, the content of the (C) sterically hindered phenol is from 0.05 to 3 parts by mass, preferably from 0.1 to 2 parts by mass, and more preferably from 0.2 to 1.5 parts by mass, per 100 parts by mass of the (A) polyamide. When the content of the sterically hindered phenol (C) is equal to or more than the above lower limit, the heat aging resistance is improved, whereas when the content of the sterically hindered phenol (C) is equal to or less than the above upper limit, bleeding out can be suppressed. In the polyamide composition of the present embodiment, from the viewpoints of heat aging resistance, mechanical properties, and suppression of bleed-out when a molded article is obtained, the weight ratio of the contents of the branched polyamine (B) and the sterically hindered phenol (C) is preferably 0.06 to 30, more preferably 0.3 to 8.0, and even more preferably 0.67 to 5.0. When the weight ratio of the contents of the branched polyamine (B) and the sterically hindered phenol (C) is equal to or greater than the above lower limit, the heat aging resistance is improved and the bleed-out of the sterically hindered phenol (C) can be prevented. On the other hand, when the weight ratio of the contents of the branched polyamine (B) and the sterically hindered phenol (C) is equal to or less than the above upper limit, the heat aging resistance and mechanical properties are improved.

[0057] <(D) Azine dye or phthalocyanine dye> The polyamide composition of the present embodiment contains (D) an azine dye or a phthalocyanine dye, which acts as a crystallization retarder, thereby further improving the appearance of the molded article.

[0058] As the azine dye, nigrosine is preferred, and as the phthalocyanine dye, copper phthalocyanine is preferred.

[0059] The (D) azine dye or phthalocyanine dye has an effect of suppressing the bleeding out of the (C) sterically hindered phenol by interacting with the (C) sterically hindered phenol. From the viewpoint of the magnitude of this bleeding out suppression effect, it is preferable to use an azine dye among the (D) components, and nigrosine is more preferable. In this case, the strong interaction between the (C) sterically hindered phenol having an amide group and nigrosine further suppresses the bleeding out of the (C) sterically hindered phenol.

[0060] [(D) Content of azine dye or phthalocyanine dye] In the polyamide composition of this embodiment, the content of the (D) azine dye or phthalocyanine dye is 0.01 part by mass or more and 0.5 part by mass or less, preferably 0.05 part by mass or more and 0.32 part by mass or less, and more preferably 0.08 part by mass or more and 0.2 part by mass or less, relative to 100 parts by mass of the (A) polyamide. By setting the content of the (D) azine dye or phthalocyanine dye to the above lower limit or more, the appearance of the molded article becomes good and the bleeding out of the (C) sterically hindered phenol can be prevented. On the other hand, by setting the content of the (D) azine dye or phthalocyanine dye to the above upper limit or less, the strength, rigidity, etc. of the molded article tend to be prevented from decreasing. In the polyamide composition of the present embodiment, the weight ratio of the content of (C) the sterically hindered phenol to the content of (D) the azine dye or the phthalocyanine dye is preferably 0.5-60, more preferably 1.0-20, and further preferably 1.67-12. By setting the weight ratio of the (C) sterically hindered phenol to the (D) azine dye or phthalocyanine dye at or above the lower limit, the tensile strength can be improved. By setting the weight ratio of the (C) sterically hindered phenol to the (D) azine dye or phthalocyanine dye at or below the upper limit, bleeding out of the (C) sterically hindered phenol can be prevented.

[0061] [Halide ion content] The (D) azine dye or phthalocyanine dye may contain halide ions. Since halide ions cause a decrease in electrical properties, the concentration of halide ions contained in the (D) azine dye or phthalocyanine dye is preferably less than 1 mass%, more preferably less than 0.6 mass%, and even more preferably less than 0.2 mass%, based on the mass of the (D) azine dye or phthalocyanine dye. Here, the concentration of halide ions is measured by combustion ion chromatography.

[0062] <(E) Carbon Black> The polyamide composition of the present embodiment may contain (E) carbon black. By containing (E) carbon black, the laser marking property can be improved. In addition, by using (D) azine dye or phthalocyanine dye together, even if (E) carbon black acts as a crystal nucleating agent, the crystallization retardation effect of (D) azine dye or phthalocyanine dye can prevent the appearance of the molded article from being impaired and improve the appearance.

[0063] Laser marking here refers to printing the product name, serial number, cautions, etc., using a laser. To enable laser marking, a black additive such as (E) carbon black is used as an additive that absorbs the laser.

[0064] However, such laser-absorbing additives can act as crystal nucleating agents and promote the crystallization of the matrix resin, which can easily impair the appearance of the molded product.

[0065] When the polyamide composition of the present embodiment is used together with component (D), even if the carbon black (E) acts as a crystal nucleating agent, the crystallization retarding effect of component (D) ensures that the appearance of the molded article is not impaired and can be made better.

[0066] Examples of (E) carbon black include acetylene black, lamp black, thermal black, furnace black, channel black, ketjen black, gas black, and oil black. These (E) carbon blacks can be used alone or in combination of two or more.

[0067] [(E) Carbon black content] In the polyamide composition of this embodiment, the content of (E) carbon black is preferably 0.01 part by mass or more and 0.5 part by mass or less, more preferably 0.05 part by mass or more and 0.25 part by mass or less, and even more preferably 0.1 part by mass or more and 0.2 part by mass or less, relative to 100 parts by mass of (A) polyamide. When the content of (E) carbon black is equal to or greater than the lower limit, the efficiency of heating by a laser is improved and the laser marking properties are good. On the other hand, when the content of (E) carbon black is equal to or less than the upper limit, carbonization of the resin due to heating can be prevented.

[0068] <(F) halide ion> In the polyamide composition of this embodiment, the concentration of (F) halide ions is 500 ppm by mass or less, preferably 400 ppm by mass or less, more preferably 300 ppm by mass or less, even more preferably 200 ppm by mass or less, and particularly preferably 100 ppm by mass or less, relative to the total mass of the polyamide composition. On the other hand, the lower limit of the concentration of the (F) halide ion is preferably as low as possible, and can be, for example, 0.0 ppm by mass, 0.1 ppm by mass, or 1 ppm by mass.

[0069] In the polyamide composition of the present embodiment, components (A) to (E) may contain halide ions as impurities depending on the manufacturing method. If the polyamide composition of the present embodiment contains more than the upper limit of the (F) halide ions, electrical properties such as volume resistivity and tracking resistance may be impaired. Therefore, by suppressing the amount of (F) halide ions contained in each of components (A) to (E) and setting the concentration of (F) halide ions contained in the polyamide composition to the upper limit or less, a polyamide composition having excellent electrical properties when molded into a molded product can be obtained.

[0070] <(G) Filler> The polyamide composition of the present embodiment preferably further contains a filler (G) in addition to the components (A) to (E). By containing the filler (G), the polyamide composition of the present embodiment can further improve mechanical properties such as strength and rigidity when molded into an article.

[0071] The (G) filler is not particularly limited, and examples thereof include glass fiber, carbon fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, glass flake, calcium carbonate, talc, kaolin, mica, hydrotalcite, zinc carbonate, calcium hydrogen phosphate, wollastonite, zeolite, boehmite, magnesium oxide, calcium silicate, sodium aluminosilicate, magnesium silicate, ketjen black, acetylene black, furnace black, carbon nanotubes, graphite, brass, copper, silver, aluminum, nickel, iron, calcium fluoride, montmorillonite, swellable fluoromica, apatite, milled fiber, etc. These (G) fillers may be used alone or in combination of two or more.

[0072] Among these, from the viewpoints of rigidity, strength, and the like, the (G) filler is preferably glass fiber, carbon fiber, glass flake, talc, kaolin, mica, calcium hydrogen phosphate, wollastonite, carbon nanotubes, graphite, calcium fluoride, montmorillonite, expandable fluoromica, or apatite. The (G) filler is more preferably one or more selected from the group consisting of glass fiber, calcium carbonate, talc, mica, wollastonite, and milled fiber, further preferably glass fiber or carbon fiber, and particularly preferably glass fiber.

[0073] When the (G) filler is glass fiber or carbon fiber, the number average fiber diameter (d1) is preferably 3 μm or more and 30 μm or less. The weight average fiber length (L) is preferably 100 μm or more and 5 mm or less. Furthermore, the aspect ratio ((L) / (d1)) of the number average fiber diameter (d1) to the weight average fiber length (L) is preferably 10 or more and 100 or less. By using glass fiber or carbon fiber having the above configuration, higher properties can be exhibited.

[0074] In addition, when the filler (G) is glass fiber, the number average fiber diameter (d1) is more preferably 3 μm or more and 30 μm or less, the weight average fiber length (L) is more preferably 103 μm or more and 5 mm or less, and the aspect ratio ((L) / (d1)) is more preferably 3 or more and 100 or less.

[0075] The number average fiber diameter and weight average fiber length of the (G) filler can be measured by the following method. First, the molded product is dissolved in a solvent in which the (A) polyamide is soluble, such as formic acid. Next, from the insoluble components obtained, for example, 100 or more (G) fillers are arbitrarily selected. Next, the (G) fillers are observed with an optical microscope, a scanning electron microscope, or the like, and the number average fiber diameter can be obtained by dividing the total measured fiber diameter by the number of (G) fillers measured. Alternatively, the weight average fiber length can be obtained by dividing the total measured fiber length by the total weight of the (G) fillers measured.

[0076] [(G) Filler content] In the polyamide composition of this embodiment, the content of the (G) filler, relative to 100 parts by mass of the (A) polyamide, is preferably 0 parts by mass or more and 150 parts by mass or less, more preferably 10 parts by mass or more and 140 parts by mass or less, even more preferably 20 parts by mass or more and 135 parts by mass or less, particularly preferably 25 parts by mass or more and 130 parts by mass or less, and most preferably 30 parts by mass or more and 100 parts by mass or less. When the content of the (G) filler is equal to or greater than the above lower limit, the mechanical properties such as strength and rigidity of the molded article tend to be improved. On the other hand, when the content of the (G) filler is equal to or less than the above upper limit, the molded article tends to have better surface appearance and laser markability. In particular, when the (G) filler is glass fiber and the content of the (G) filler is within the above range per 100 parts by mass of the (a) polyamide, the mechanical properties such as strength and rigidity of the molded article tend to be further improved.

[0077] <Other additives> The polyamide composition may contain other additives commonly used in polyamides, provided that the purpose of the present embodiment is not impaired. Examples of the other additives include fibrillating agents, lubricants, fluorescent bleaching agents, plasticizers, UV absorbers, antistatic agents, flow improvers, reinforcing agents, spreading agents, nucleating agents, rubbers, reinforcing agents, other polymers, etc. The content of the other additives in the polyamide composition of the present embodiment may be appropriately determined by a person skilled in the art depending on the purpose.

[0078] <Method of producing polyamide composition> In the method for producing the polyamide composition, the method for adding each of the constituent components is not particularly limited, so long as it is a method in which components (A) to (E) are mixed with, as necessary, component (G) and other additives described above.

[0079] Examples of methods for mixing the constituent materials include a method in which the constituent materials are mixed using a Henschel mixer or the like and then fed to a melt kneader and kneaded therein, and a method in which component (A) and components (B) to (E) that have been melted in a single-screw or twin-screw extruder are fed from a top feeder, and a filler (C) and other additives (D) are fed, as necessary, from a side feeder.

[0080] The components constituting the polyamide composition may be supplied to the melt kneader by supplying all of the components at once through the same supply port, or by supplying components (A) to (E) and, if necessary, component (G) through different supply ports.

[0081] The melt-kneading temperature is preferably about 250° C. or more and 375° C. or less in terms of the resin temperature.

[0082] The melt-kneading time is preferably about 0.5 to 5 minutes.

[0083] The melt-kneading device is not particularly limited, and known devices, for example, melt-kneaders such as single-screw or twin-screw extruders, Banbury mixers, and mixing rolls, can be used. <Polyamide composition (2)> Another embodiment of the polyamide composition of the present invention comprises: (A) a polyamide; and (B) a branched polyamine in an amount of 0.1 part by mass or more and 3 parts by mass or less per 100 parts by mass of the (A) polyamide. The viscosity of the branched polyamine (B) at 20° C. measured by a Brookfield viscometer in accordance with ISO 2555 is 1000 mPa·s or more and 2500 mPa·s or less.

[0084] The polyamide composition of the present embodiment has the above-mentioned configuration, and thus can give a molded article that is excellent in heat aging resistance, electrical properties, appearance, and mechanical properties, and in which additives are unlikely to dissolve in water.

[0085] Each component of the polyamide composition of the present embodiment will be described in detail below. [(A) Polyamide] In the polyamide composition of the present embodiment, the polyamide (A) is as described in <Polyamide (A)> of <Polyamide composition (1)> above.

[0086] [(B) Branched polyamine] In the polyamide composition of the present embodiment, the branched polyamine (B) is as described in <Branched polyamine (B)> of <Polyamide composition (1)> above.

[0087] [(C) Organic heat stabilizer] The polyamide composition of the present embodiment may contain an organic heat stabilizer (C). By containing the organic heat stabilizer (C), it is possible to improve the heat aging resistance when the polyamide composition is made into a molded article. In the polyamide composition of this embodiment, from the viewpoint of heat aging resistance and suppression of bleed-out when formed into a molded article, the content of the (C) organic heat stabilizer is preferably from 0.05 to 3 parts by mass, more preferably from 0.1 to 2 parts by mass, and particularly preferably from 0.2 to 1.5 parts by mass, per 100 parts by mass of the (A) polyamide.

[0088] When the content of the (C) organic heat stabilizer is equal to or more than the above lower limit, the heat aging resistance is improved, whereas when the content of the (C) organic heat stabilizer is equal to or less than the above upper limit, bleeding out can be suppressed.

[0089] The (C) organic heat stabilizer is not particularly limited, but for example, a sterically hindered phenol-based organic heat stabilizer, a phosphorus-based organic heat stabilizer, an aromatic amine-based organic heat stabilizer, a sterically hindered amine-based organic heat stabilizer, etc. can be used. Among them, the (C) organic heat stabilizer is preferably a sterically hindered phenol-based organic heat stabilizer. The sterically hindered phenol-based organic heat stabilizer may be referred to as "(C1) sterically hindered phenol". The (C1) sterically hindered phenol is as described in <(C) sterically hindered phenol> in the above-mentioned <Polyamide composition (1)>.

[0090] [(D) Azine dye or phthalocyanine dye] In the polyamide composition of the present embodiment, the (D) azine dye or phthalocyanine dye is as described in <(D) Azine dye or phthalocyanine dye> in <Polyamide composition (1)> above.

[0091] [(E) Carbon black] In the polyamide composition of the present embodiment, the (E) carbon black is as described in <(E) Carbon Black> in <Polyamide Composition (1)> above. However, in the polyamide composition of this embodiment, the content of (E) carbon black is 0.001 part by mass or more and 0.5 part by mass or less, preferably 0.005 part by mass or more and 0.25 part by mass or less, and more preferably 0.01 part by mass or more and 0.2 part by mass or less, per 100 parts by mass of (A) polyamide. When the content of (E) carbon black is equal to or greater than the lower limit, the efficiency of heating by a laser is improved and the laser marking properties are good. On the other hand, when the content of (E) carbon black is equal to or less than the upper limit, carbonization of the resin due to heating can be prevented.

[0092] [(F) Halide ion] In the polyamide composition of the present embodiment, the (F) halogenide ion is as described in <(F) halogenide ion> in <Polyamide composition (1)> above.

[0093] [(G) Filler] In the polyamide composition of the present embodiment, the (G) filler is as described in <(G) filler> of the above-mentioned <Polyamide composition (1)>.

[0094] <Usage> Molded articles obtained from the polyamide composition according to the embodiment of the present invention are suitable for use as material parts for various applications, such as automobiles, mechanical industry, electrical and electronics, industrial materials, construction materials, daily necessities and household goods, etc. Among them, they are particularly suitable for use as automobile parts because of their excellent heat aging resistance and electrical properties. EXAMPLES

[0095] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples. Each of the components of the resin compositions used in the examples and comparative examples will be described below. Hereinafter, Examples 13 to 20 are considered as reference examples.

[0096] <Components> [(A) Polyamide] A-1: Polyamide 66 (PA66) A-2: Polyamide 66 (PA66) A-3: Polyamide 6 (PA6) (Ube Industries, SF1013)

[0097] The synthesis methods of polyamides A-1 and A-2 will be described later. The obtained polyamides A-1 and A-2 were dried in a nitrogen stream and adjusted to a moisture content of about 0.1% by mass before being used as raw materials for the polyamide composition.

[0098] [(B) Branched polyamine] B-1: Lupasol (registered trademark) FG (manufactured by BASF, weight average molecular weight 800, viscosity 1680 mPa·s) B-2: Epomin (registered trademark) SP-006 (manufactured by Nippon Shokubai Co., Ltd., number average molecular weight 600, viscosity 2900 mPa s) B-3: Lupasol (registered trademark) G20 WF (manufactured by BASF, weight average molecular weight 1300, viscosity 8000 mPa s) B-4: Epomin (registered trademark) SP-003 (manufactured by Nippon Shokubai Co., Ltd., number average molecular weight 300, viscosity 300 mPa·s)

[0099] [(C) Sterically hindered phenol] C-1: N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) (manufactured by BASF, product name "Irganox (registered trademark) 1098", contains an amide group) C-2: 3,9-Bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (ADEKA Corporation, trade name "ADEKA STAB (registered trademark) AO-80", no amide group)

[0100] [(C') Heat stabilizer] C'-1: Hindered amine heat stabilizer (manufactured by Clariant, product name "Nylostab (registered trademark) S-EED") C'-2: Aromatic amine-based heat stabilizer (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac CD") C'-3: Aromatic amine-based heat stabilizer (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac 224") C'-4: Mixture of copper iodide and potassium iodide

[0101] [(D) Azine dye or phthalocyanine dye] D-1: Nigrosine dye (manufactured by Orient Chemical Co., Ltd., TH807) (halide ion concentration: 0.06% by mass) D-2: Nigrosine dye (manufactured by Orient Chemical Co., Ltd., TH870) (halide ion concentration: 1.6% by mass)

[0102] [(E) Carbon black] E-1: Carbon black (primary particle size 27 nm)

[0103] [(G) Filler] G-1: Glass fiber (GF) (manufactured by Nippon Electric Glass, product name "ECS03T275H", average fiber diameter 10 μm, cut length 3 mm)

[0104] <(A) Synthesis of Polyamide> [Synthesis Example 1] (Synthesis of Polyamide A-1 (PA66)) The polymerization reaction of polyamide was carried out by the "thermal melt polymerization method" as follows. First, 1500 g of an equimolar salt of adipic acid and hexamethylenediamine was dissolved in 1500 g of distilled water to prepare a homogeneous aqueous solution of 50% by mass of the raw material monomer. This aqueous solution was charged into an autoclave with an internal volume of 5.4 L and substituted with nitrogen. Next, the solution was concentrated by gradually removing steam to a solution concentration of 70% by mass while stirring at a temperature of 110°C to 150°C. Next, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8 MPa. The reaction was continued for 1 hour while gradually removing steam to maintain the pressure at 1.8 MPa until the internal temperature reached 245°C. Next, the pressure was reduced over 1 hour. Next, the inside of the autoclave was maintained under a reduced pressure of 650 torr (86.66 kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C. Next, the mixture was pressurized with nitrogen and formed into a strand from the lower spinneret (nozzle), water-cooled, cut, and discharged in the form of pellets, which were then dried at 100°C in a nitrogen atmosphere for 12 hours to obtain Polyamide A-1 (PA66). The resulting polyamide A-1 (PA66) had a weight average molecular weight of 35,000 and a molecular weight distribution (Mw / Mn) of 2.0.

[0105] [Synthesis Example 2] (Synthesis of Polyamide A-2 (PA66)) The polymerization reaction of polyamide was carried out by the "thermal melt polymerization method" as follows. First, 1500 g of an equimolar salt of adipic acid and hexamethylenediamine was dissolved in 1500 g of distilled water to prepare a homogeneous aqueous solution of 50% by mass of the raw material monomers. This aqueous solution was charged into an autoclave with an internal volume of 5.4 L. Copper iodide and potassium iodide were added thereto and replaced with nitrogen. Next, the solution was concentrated by gradually removing steam to a solution concentration of 70% by mass while stirring at a temperature of 110°C to 150°C. Next, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8 MPa. The reaction was continued for 1 hour while gradually removing steam and maintaining the pressure at 1.8 MPa until the internal temperature reached 245°C. Next, the pressure was lowered over 1 hour. Next, the inside of the autoclave was maintained under a reduced pressure of 650 torr (86.66 kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C. Next, the mixture was pressurized with nitrogen and formed into a strand from the lower spinneret (nozzle), water-cooled, cut, and discharged in the form of pellets, which were then dried at 100°C in a nitrogen atmosphere for 12 hours to obtain polyamide A-2 (PA66). The resulting polyamide A-2 (PA66) had a weight average molecular weight of 35,000 and a molecular weight distribution (Mw / Mn) of 2.0.

[0106] <Production of polyamide composition> [Examples 1 to 22 and Comparative Example 1] Using a TEM35mm twin-screw extruder (set temperature: 290°C, screw rotation speed: 300 rpm) manufactured by Toshiba Machine Co., Ltd., the components (A), (B), (C) or (C'), (D), and (E) were fed from the top feed port provided at the most upstream part of the extruder so as to obtain the blending amounts shown in Tables 1 to 4. The component (G) was fed from the side feed port on the downstream side of the extruder (when the resin fed from the top feed port was in a sufficiently molten state). The molten mixture extruded from the die head was then cooled in the form of strands and pelletized to obtain pellets of the polyamide composition.

[0107] <Method of measuring physical properties> [Physical Properties 1] (Halide ion concentration) Halide ions (Cl) contained in the pellets of the polyamide composition - , Br - , I - The concentration of ) was quantified by combustion ion chromatography. Specifically, a Mitsubishi Chemical Analytech AQF-2100H was used, and samples were prepared by the combustion tube combustion method using ultrapure water (containing hydrogen peroxide and hydrazine hydrate) as the absorption liquid. The ion chromatography (IC) device used was a Thermo Fisher Scientific Integrion RFIC, the column was a Thermo Fisher Scientific IonPac AS18-4μm (4mmφ×150mm), the eluent was a KOH aqueous solution, and the detector was a UV detector.

[0108] From the measurement results, the halide ions (Cl - , Br - , I - Specifically, the concentration of Cl was calculated using the following formula: - , Br - , and I - The concentration of each in the sample was calculated, and the sum of these values ​​was regarded as the concentration of halide ions.

[0109] "Cl - , Br - , or I - Concentration (ppm by mass) = [(IC measurement value (mg / L)) × (dilution rate) – (blank IC measurement value (mg / L))] × [(amount of absorption solution (mL)) / 1000] × [1000000 / (mass of sample (mg))]

[0110] <Evaluation method> [Manufacturing of multipurpose test specimens] The pellets of the polyamide composition were dried in a nitrogen stream to reduce the moisture content in the polyamide composition to 500 mass ppm or less. Next, the pellets of each polyamide composition with the adjusted moisture content were molded into a multipurpose test piece (A-type, dumbbell-shaped tensile test piece) in accordance with ISO3167 using an injection molding machine (PS-40E, manufactured by Nissei Plastics Co., Ltd.). The dimensions of the multipurpose test piece were: total length ≧170 mm, distance between tabs 109.3±3.2 mm, length of parallel part 80±2 mm, radius of shoulder 24±1 mm, width of end 20±0.2 mm, width of central parallel part 10±0.2 mm, and thickness 4±0.2 mm. Specific injection molding conditions were set as follows: injection and pressure holding time: 25 seconds, cooling time: 15 seconds, mold temperature: 80°C, and cylinder temperature: 290°C.

[0111] [Rating 1] (Tensile strength and heat aging resistance) Using the multipurpose test piece (A type), a tensile test was performed at a tensile speed of 5 mm / min in accordance with ISO527, and the initial tensile strength (MPa) was measured (S0). Next, each multipurpose test piece (A type) was placed in an oven in accordance with ISO188, and heated at 180°C for 2000 hours, respectively, to perform a heat aging test. After 2000 hours, each multipurpose test piece (A type) was removed from the oven and cooled at 23°C for 24 hours. Next, a tensile test was performed at a tensile speed of 5 mm / min in accordance with ISO527 in accordance with each multipurpose test piece (A type) after the heat aging test, and the tensile strength (MPa) after the heat aging test was measured (S1). Next, the tensile strength retention rate (%) was calculated using the formula shown below.

[0112] "Tensile strength retention rate (%)" = S1 / S0 x 100

[0113] [Manufacturing of flat plate molded products] A slab molded article was produced as follows. Using an injection molding machine (NEX50III-5EG, manufactured by Nissei Plastic Industrial Co., Ltd.), the cooling time was set to 25 seconds, the screw rotation speed to 200 rpm, the mold temperature to 80°C, and the cylinder temperature to 290°C. The injection pressure and injection speed were appropriately adjusted so that the filling time was in the range of 1.6±0.1 seconds, and a flat molded product (6 cm x 9 cm, thickness 2 mm) was produced.

[0114] [Rating 2] (Tracking resistance) The flat molded products were tested in accordance with IEC 60112 using a tracking resistance tester (manufactured by Yamayo Test Instruments Co., Ltd.) to calculate the tracking resistance index (CTI). The higher the tracking resistance index (CTI), the better the electrical properties were determined to be.

[0115] [Rating 3] (Volume resistivity) The volume resistivity of the molded flat plate was measured according to ASTM D257. It was determined that the higher the volume resistivity, the better the electrical properties.

[0116] [Rating 4] (Surface appearance) The central part of the molded plate was measured for 60 degree gloss using a gloss meter (HORIBA IG320) in accordance with JIS-K7150. The higher the gloss value, the better the surface appearance was judged to be.

[0117] [Rating 5] (Bleed-out test) When (C) sterically hindered phenol or (C') heat stabilizer is contained and the color of the molded product is black, bleeding out of (C) sterically hindered phenol or (C') heat stabilizer becomes visible. Bleeding out tests were conducted when (C) sterically hindered phenol or (C') heat stabilizer is contained and (D) azine dye or phthalocyanine dye or (E) carbon black is also contained. A molded plate was used and left to stand in a thermo-hygrostat (temperature: 80°C, relative humidity: 95%) for 500 hours. The molded plate was removed and the bleeding on the surface was observed, and the likelihood of bleeding out was evaluated according to the following criteria. In the table, this is indicated as "bleed-out suppression."

[0118] (Evaluation Criteria) ⊚: No bleeding was observed in the flat molded product. ◯: Bleeding was observed in some parts of the plate molded product. Δ: Bleeding was observed over the entire flat molded product. ×: A large amount of bleeding was observed over the entire flat molded product.

[0119] [Rating 6] (Laser marking properties) The flat molded product was laser-marked with a 3 mm x 3 mm square marking using a MD-V9920 or MD-S9910 manufactured by Keyence Corporation. The laser marking conditions were a wavelength of 1064 nm and an output of 7.8 W. The laser-marked part was observed, and the laser marking properties were evaluated as follows.

[0120] (Evaluation Criteria) ○: The laser marked area appears white. ×: The laser marked area does not appear white.

[0121] [Rating 7] (Charpy impact strength) The polyamide composition molded articles (multipurpose test pieces) obtained in the Examples and Comparative Examples were used to measure the notched Charpy impact strength in accordance with ISO 179.

[0122] [Rating 8] (Evaluation of the resistance of additives to dissolution in water) 30 g of polyamide composition pellets and 30 g of distilled water were placed in a 100 mL plastic bottle, sealed, and left in an electric oven at 80°C for 24 hours. After cooling, the water in the plastic bottle was removed into a beaker, and the pH at 23°C was measured with a pH meter. Since the (B) polyethyleneimine aqueous solution is basic, it was determined that the closer the pH value was to 7, the less likely (B) polyethyleneimine was to be eluted into water. In the table, this is indicated as the pH of the eluted water.

[0123] For each polyamide composition, the above-mentioned methods for measuring and evaluating physical properties were carried out. The results are shown in Tables 1 to 4. The tensile strengths shown in the tables are initial tensile strengths (S0) (MPa).

[0124] [Table 1]

[0125] [Table 2]

[0126] [Table 3]

[0127] [Table 4] [Industrial Applicability]

[0128] According to the polyamide composition of the present embodiment, it is possible to obtain a molded article having excellent mechanical properties, heat aging resistance at 180°C for a long period of about 2000 hours, and electrical properties, and additive bleed-out at 80°C and a relative humidity of 95% is suppressed, so that additives are unlikely to dissolve in water, and the molded article has excellent appearance. The molded article obtained from the polyamide composition of the present embodiment is suitably used as a material part for various applications such as automobiles, mechanical industry, electrical and electronics, industrial materials, industrial materials, building materials, daily necessities and household goods, etc.

Claims

1. (A) a polyamide; Relative to 100 parts by mass of the polyamide (A), 0.1 parts by mass or more and 3 parts by mass or less of a branched polyamine (B); 0.05 parts by mass or more and 3 parts by mass or less of (C) a sterically hindered phenol; (D) an azine dye or a phthalocyanine dye in an amount of from 0.01 parts by mass to 0.5 parts by mass; A polyamide composition comprising: A polyamide composition, having a concentration of (F) halide ions of 500 ppm by mass or less relative to the total mass of the polyamide composition, as measured by combustion ion chromatography.

2. The polyamide (A) includes polyamide 66, 2. The polyamide composition according to claim 1, wherein the content of polyamide 66 is 50 mass% or more based on the total mass of the polyamide (A).

3. The polyamide composition according to claim 1 or 2, wherein the branched polyamine (B) is a polyethyleneimine homopolymer or copolymer.

4. The polyamide composition according to claim 1 or 2, wherein the branched polyamine (B) has a weight average molecular weight of 400 or more and 2,000 or less.

5. 3. The polyamide composition according to claim 1 or 2, wherein the (C) sterically hindered phenol contains one or more amide groups.

6. The polyamide composition according to claim 1 or 2, further comprising (E) 0.01 part by mass or more and 0.5 part by mass or less of carbon black relative to 100 parts by mass of the polyamide (A).

7. 3. The polyamide composition according to claim 1 or 2, wherein the concentration of (F) halide ions, as measured by combustion ion chromatography, is less than 1 mass % relative to the mass of (D) the azine dye or the phthalocyanine dye.

8. The polyamide composition according to claim 1 or 2, wherein a weight ratio of the branched polyamine (B) to the sterically hindered phenol (C) is 0.06 to 30, and a weight ratio of the sterically hindered phenol (C) to the azine dye or phthalocyanine dye (D) is 0.5 to 60.

9. The polyamide composition according to claim 1 or 2, further comprising (G) a filler.

Citation Information

Patent Citations

  • JP1973017864B1

  • Polyamide resin particle containing heat resisting agent and its production

    JP1996325382A

  • Resin composition for insulation film and insulation film using the composition

    JP2002146076A

  • Composition containing prepolymer and crosslinking agent, method for producing the same and use thereof

    JP2006348293A

  • Heat aging resistant polyamide

    JP2008530290A

Cited By

  • Polyamide composition

    JP2025105656A